Tingkat Pengetahuan Masyarakat dalam Kesiapsiagaan Bencana di Indonesia - Ajeng Purwati Ningtyas (Prodi PWK Universitas Tadulako, 2026)
Indonesia is among the countries with the highest natural disaster risk due to its location at the convergence of three tectonic plates and within the Pacific Ring of Fire. Although Indonesia has established regulatory and institutional frameworks for disaster management, limited public understanding of disaster risks remains a major barrier to effective preparedness. This study examines the level of community disaster-risk knowledge and its influence on disaster preparedness. A quantitative survey was conducted involving 155 respondents selected through accidental sampling. Data were collected through an online five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that community knowledge has a positive and significant effect on disaster preparedness (β = 0.712; t = 12.068; p < 0.001), explaining 50.7% of the variance in preparedness (R² = 0.507). The average knowledge score was moderate (mean = 3.56), with a declining trend across higher cognitive dimensions, from knowing to analysis. The lowest preparedness indicator was ownership of a Disaster Readiness Bag/Tas Siaga Bencana (mean = 2.95), indicating limited public adoption of BNPB recommendations. These results highlight the need for disaster education programs that not only provide factual information but also strengthen individuals’ capacity to apply and analyze disaster risks. The study supports the Sendai Framework for Disaster Risk Reduction 2015–2030, particularly its first priority of understanding disaster risk as the foundation of preparedness.